Everything feels just a little heavier, more wrought with implications, you know? – a mixed-methods study examining lifestyle behaviors, health, and well-being of pregnant and postpartum women during the early months of the COVID-19 pandemic - Sara Dube; Muhammad Asim; Jennifer Gonzalez; Gracia Dala; Michelle L. Wright; Megan J. Gray; Linda G. Kahn; Deborah Jacobvitz; Elizabeth M. Widen (BMC Pregnancy and Childbirth)
Abstract Background While the striking impact of the COVID-19 pandemic on mental health, heath care access and lifestyle behaviors, including perceived health, diet, physical activity, and sleep has been reported, few studies have examined these domains jointly among pregnant and postpartum people in the early stages of the COVID-19 pandemic. Methods This mixed methods study was conducted among a subset of participants (n = 22) in a cohort study in Austin, Texas, who were pregnant or had recently delivered when the outbreak occurred. Measures were from the early second trimester up to 6 months postpartum. Findings from questionnaires were complemented by qualitative interviews during Spring/Summer 2020 regarding experiences during the early pandemic. Results From our quantitative data (n = 22), most participants reported that the pandemic generally had a negative impact on their lives (81%), that they shifted to eating more at home (71%), and that they were less physically active (62%). Five major themes emerged in our qualitative interviews (n = 22): (1) adaptation to pandemic restrictions; (2) psychosocial experiences, such as feelings of anxiety, guilt, sadness, isolation, and frustration; (3) health behavior changes; (4) health care experiences; and (5) where they obtained general and perinatal related pandemic information. Of those who completed both pregnancy and postpartum interviews (n = 8), all reported anxiety during both periods; however, those who delivered in Spring 2020 experienced more anxiety surrounding delivery and less social support than those who delivered in Summer 2020, who reported less anxiety surrounding hospital birth and greater social support, particularly after delivery. Conclusions Overall, our findings confirm prior evidence that the COVID-19 pandemic had a marked impact on stress, anxiety, and worries, as well as lifestyle behaviors among pregnant and postpartum people. Our work provides lessons for health care practitioners about support need for pregnant and postpartum persons amid societal disruption.